THE SUBJECT OF WRONGS: Crime, Populism, and Venezuela’s Punitive Turn - SAMET, ROBERT (Cultural anthropology, 2019)
This article draws on research in Venezuela to make a broader argument about the link between populism and injury. Specifically, it considers the role that crime victimhood plays in the rise of punitive populism or the so-called punitive turn. Under President Hugo Chávez, the Venezuelan government publicly denounced tough-on-crime policies as instruments of socioeconomic oppression. Following Chávez’s death, there was an abrupt change of course due, in part, to the opposition’s mobilization of crime victims. The Venezuelan case illustrates a double bind that confronts scholars who are critical of the punitive turn. On the one hand, the figure of the crime victim mediates the body politic in a way that reproduces structures of racial and economic domination. On the other hand, the failure to substantively address the material injuries of crime victims propels grassroots support for punitive populism. Instead of focusing on the subject of rights, this article proposes starting with the subject of wrongs as a bottom-up approach to political subjectivity that can help us understand the dynamic behind punitive populism and show us a way out of the double bind. Este artículo se basa en trabajo de campo en Venezuela y persigue establecer un argumento general sobre el vínculo entre el populismo y el daño. Específicamente, el artículo considera el papel que las víctimas del crimen desempeñan en el auge del populismo punitivo o el giro punitivo. Durante el gobierno de Hugo Chávez se denunciaba la política de mano dura como un instrumento de opresión socioeconómica. Tras la muerte de Chávez, hubo un cambio abrupto en esta práctica debido, en parte, a la movilización de las víctimas del crimen. El caso venezolano constituye un dilema para los académicos que critican el giro punitivo. Por un lado, la figura de la víctima participa en el cuerpo político de una manera que reproduce estructuras de dominación racial y económica. Por otro lado, la incapacidad para responder efectivamente a los reales daños del crimen aumenta el apoyo popular a la política de mano dura. En vez de enfocarse en el tema de los derechos, este artículo propone enfocarse en el tema de los males (o daños) como una manera de abordar la subjetividad política que podría, por un lado ayudarnos a entender la dinámica detrás del populismo punitivo, y por el otro encontrar una solución al dilema que este plantea.